Association of BMI with Breast Cancer: An Experience at a Tertiary Healthcare in a Developing Country - Umm-E-Habiba Abdul Rauf, Omema Saleem, Mujeeb Rehman Malik, Summaya Saeed, Karim Rizwan Nathani, Faisal Ghani Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Breast carcinoma is the most common invasive cancer in females, and second leading cause of global cancer mortality.1 The incidence of this disease remains high in our population. It is therefore essential to identify and control common risk factors. This case-control study was conducted to determine the relationship between BMI and breast cancer. Materials and Methods: A prospective case control study was performed between the time duration of September 2021 till February 2022. A total no of 158 patients, out of which 79 of them were part of the control group, while the remaining 79 had breast cancer were included in this study. Patient’s BMI and other risk factors were contrasted with these groups using stata 14.2. Results: Multivariate logistic regression analysis revealed that of the preoperative factors; age greater than 40 years(95%CI, 1.01 4.87), and postmenopausal status (95%CI, 1.10 9.70) were all independently associated with higher incidence of breast cancer in our women. BMI association with breast cancer was also considered significant with 95% confidence interval around 1 (95%CI, 0.20 1.14). Family history and breast cancer had no independent associated with each other. When only the tumor stage were compared, higher stage of disease was associated with delayed presentation. Conclusions: higher BMI, low parity and higher number of miscarriages cumulatively predispose the postmenopausal women of this region to higher risk of breast cancer.